Γ. X. Xιονίδη, Εμμανουήλ Ιω. Ζάχος (1860-1924) ένας Βεροιώτης εκπαιδευτικός κατά τους χρόνους της Τουρκοκρατίας. Πρόλογος Στ. Εμμ. Ζάχου - Γιαράλη-Παπαδοπούλου, Δέσποινα (Μακεδονικά, 1975)
No abstract